Quality Attributes of Wheat-Tigernut Flour Blends and Chin-Chin Produced From the Blends (IPS Journal of Nutrition and Food Science, 2024)
This study evaluated the physicochemical, functional and proximate composition of wheat and tigernut composite flour; and proximate composition and sensory properties of Chin-chin produced from the wheat-tigernut flours blends. The addition of tigernut flour to wheat was 10, 20, 30 and 40% representing sample A – D while 100% wheat flour (sample E) served as control. Analyses were by standard analytical procedures. pH, titratable acidity and viscosity of the flour samples ranged from 4.03 - 4.37, 0.39 - 0.80 %Lactic acid, and 9.38 - 9.58 Pa.s respectively, while sugar was 1.00 0Brix across all samples. Oil absorption capacity, water absorption capacity, dispersibility, solubility index, swelling power, bulk density and foaming capacity varied respectively from 1.22 - 1.40 g/g 1.14 - 1.34 g/g, 2.00 - 4.13%, 35.00 - 37.00 g/g, 6.45 - 7.48 g/g, 0.83 - 0.90 g/ml and 5.00 - 20.00%. Proximate composition of the flour blends varied respectively, from 5.55 - 8.79, 9.28-18.36, 2.12 - 10.91, 1.70 - 2.01, 1.31- 4.17 and 64.78-74.06% for moisture, protein, fat, ash, crude fibre, and % carbohydrates. While energy value of the flours ranged from 351.89 - 405.32 kcal/100g. Chin-chin had moisture, protein, fat, ash, crude fibre, carbohydrate and energy contents of 1.85 - 8.64, 10.06 - 16.18, 24.25 - 34.29, 1.20 - 1.70, 14.65 - 27.42, 20.79 - 41.65% and 418.03 - 493.27 kcal/100g respectively. Assessor’s degree of likeness for the chin-chin ranged from 2.85 - 7.15, 3.56 - 7.85, 3.05 - 6.60, 3.25 - 7.10, 3.65 - 8.00 and 3.06 - 7.26 respectively, for aroma, appearance, colour, crunchiness, taste, and overall acceptability. Tigernut inclusion led to a significant (p
Keywords: Chin-chin; tigernut flour; proximate composition; physicochemical; functional and sensory properties